2023
DOI: 10.3390/a16050232
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning-Based Model for Hurricane Storm Surge Forecasting in the Lower Laguna Madre

Abstract: During every Atlantic hurricane season, storms represent a constant risk to Texan coastal communities and other communities along the Atlantic coast of the United States. A storm surge refers to the abnormal rise of sea water level due to hurricanes and storms; traditionally, hurricane storm surge predictions are generated using complex numerical models that require high amounts of computing power to be run, which grow proportionally with the extent of the area covered by the model. In this work, a machine-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The cell state is the pathway for information transfer, allowing it to be passed on through the sequence. A host of studies have explored the potential of LSTM for predicting storm surges and have demonstrated that LSTM models can effectively capture temporal patterns and dependencies between sequential values [46,47,49,64,81,92,100,102,[128][129][130]. For instance, Wei and Nguyen [87] proposed an encoder-decoder LSTM neural network model for predicting time-varying storm surges, showcasing its versatility in predicting storm surges generated by bypassing and landfalling storms of different sizes and intensities.…”
Section: Lstmmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell state is the pathway for information transfer, allowing it to be passed on through the sequence. A host of studies have explored the potential of LSTM for predicting storm surges and have demonstrated that LSTM models can effectively capture temporal patterns and dependencies between sequential values [46,47,49,64,81,92,100,102,[128][129][130]. For instance, Wei and Nguyen [87] proposed an encoder-decoder LSTM neural network model for predicting time-varying storm surges, showcasing its versatility in predicting storm surges generated by bypassing and landfalling storms of different sizes and intensities.…”
Section: Lstmmentioning
confidence: 99%
“…The featured convolutional layers have multiple kernels to extract useful spatial information from the input data. Many studies have utilized CNNs for storm surge prediction [47,48,78,92,129,130]. For instance, Tiggeloven et al [92] showed that CNNs could be enhanced the most when increasing the number of spatial footprints or hidden layers in the model architecture and outperforming LSTMs.…”
Section: Cnnmentioning
confidence: 99%
See 1 more Smart Citation